2007
DOI: 10.1016/j.jtcvs.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Two-year general and neurodevelopmental outcome after neonatal complex cardiac surgery in patients with deletion 22q11.2: A comparative study

Abstract: Neonates affected by deletion 22q11.2 and having neonatal complex cardiac surgery have significantly worse neurodevelopmental outcome than do those without deletion 22q11.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Although some studies indicate 22q11DS patients have worse outcome due to their multiple medical problems, 54 most studies have found the surgical results are not significantly different. 55,56 Once the diagnosis is made, immunologic evaluation is also recommended. Only the most severely immune deficient patients (Ͻ0.5%) require bone marrow or thymus transplantation, which seems to be effective in restoring normal immune function.…”
Section: Treatment Of the Diseasementioning
confidence: 99%
“…Although some studies indicate 22q11DS patients have worse outcome due to their multiple medical problems, 54 most studies have found the surgical results are not significantly different. 55,56 Once the diagnosis is made, immunologic evaluation is also recommended. Only the most severely immune deficient patients (Ͻ0.5%) require bone marrow or thymus transplantation, which seems to be effective in restoring normal immune function.…”
Section: Treatment Of the Diseasementioning
confidence: 99%
“…The global delays and variations in intelligence and/or psychomotor development found in patients with del22q11.2 are not attributed to the cardiac condition or its treatment alone: they probably represent an independent component of the syndrome itself or result from the interaction between the syndrome and its treatment [Maharasingam et al, 2003;Gerdes et al, 1999]. It has been reported that comparison of neurodevelopmental outcome following cardiac surgery between children with del22q11.2 and peers without del22q11.2 shows significantly lower mental and psychomotor developmental indices scores, significantly higher rates of motor and mental delay, and lower intelligence quotient (IQ) scores in those with del22q11.2 [Forbess et al, 2002;Swillen et al, 2005;Atallah et al, 2007]. Furthermore, such difference is independent of the age at surgery, and it has been reported also in patients undergoing surgery as neonates [Atallah et al, 2007].…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…It has been reported that comparison of neurodevelopmental outcome following cardiac surgery between children with del22q11.2 and peers without del22q11.2 shows significantly lower mental and psychomotor developmental indices scores, significantly higher rates of motor and mental delay, and lower intelligence quotient (IQ) scores in those with del22q11.2 [Forbess et al, 2002;Swillen et al, 2005;Atallah et al, 2007]. Furthermore, such difference is independent of the age at surgery, and it has been reported also in patients undergoing surgery as neonates [Atallah et al, 2007]. These data suggest that the adverse outcomes for patients with del22q11.2 are strongly associated with the chromosomal abnormality and are associated to a lesser extent with the cardiac surgery and related events.…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…29 The chromosome 22q11.2 deletion syndrome has been demonstrated to be a significant risk factor for diminished neurodevelopmental outcome. 30 More subtle genetic variations such as apolipoprotein E genotype may also be important determinants of neurological and behavioral outcomes. 31 These findings help explain the well-described clinical scenario in which 2 patients with identical congenital heart defects and identical risk factors respond differently during the perioperative period.…”
Section: Challenge: Genetic and Genomic Factorsmentioning
confidence: 99%